ChunkStash: Speeding Up Inline Storage Deduplication Using Flash Memory - Debnath, Biplob; Sengupta, Sudipta; Li, Jin (Microsoft Research, 2010)
Storage deduplication has received recent interest in the research community. In scenarios where the backup process has to complete within short time windows, inline deduplication can help to achieve higher backup throughput. In such systems, the method of identifying duplicate data, using disk-based indexes on chunk hashes, can create throughput bottlenecks due to disk I/Os involved in index lookups. RAM prefetching and bloom-filter based techniques used by Zhu et al. (2008) can avoid disk I/Os on close to 99% of the index lookups. Even at this reduced rate, an index lookup going to disk contributes about 0.1msec to the average lookup time – this is about 1000 times slower than a lookup hitting in RAM. We propose to reduce the penalty of index lookup misses in RAM by orders of magnitude by serving such lookups from a flash-based index, thereby, increasing inline deduplication throughput. Flash memory can reduce the huge gap between RAM and hard disk in terms of both cost and access times and is a suitable choice for this application. To this end, we design a flash-assisted inline deduplication system using ChunkStash, a chunk metadata store on flash. ChunkStash uses one flash read per chunk lookup and works in concert with RAM prefetching strategies. It organizes chunk metadata in a log-structure on flash to exploit fast sequential writes. It uses an in-memory hash table to index them, with hash collisions resolved by a variant of cuckoo hashing. The in-memory hash table stores (2-byte) compact key signatures instead of full chunk-ids (20-byte SHA-1 hashes) so as to strike tradeoffs between RAM usage and false flash reads. Further, by indexing a small fraction of chunks per container, ChunkStash can reduce RAM usage significantly with negligible loss in deduplication quality. Evaluations using real-world enterprise backup datasets show that ChunkStash outperforms a hard disk index based inline deduplication system by 7x-60x on the metric of backup throughput (MB/sec).